Tungsten Carbide Synthesized by Polystyrene Sphere Template Method Promoting Pd Electrocatalyst for Alcohol Oxidation in Alkaline Media. Issue 2 (16th March 2015) - Yan, Z.; Gu, Y.; Wei, W.; Jiang, Z.; Xie, J.; Shen, P. K.
Abstract Tungsten carbide (WC) particles loading on hollow carbon spheres (HCS) have been synthesized by using ammonium metatungstate as W source, glucose as carbon source, P123 as dispersant and polystyrene sphere as template. The typical WC‐HCS composite has the WC particle sizes of 5–20 nm, specific surface area of 445 m2 g−1, pore volume of 0.24 cm3 g−1 and hollow spherical structure. The above structures of WC‐HCS favor dispersion of Pd particles and mass transfer. Therefore, the Pd/WC‐HCS electrocatalyst has 4.6 times higher peak current density and 130 mV more negative onset potential than that of Pd/C for ethanol oxidation in alkaline solution. The mass transfer property of WC‐HCS (due to structure effect) and promotion effect of WC on Pd are believed to be the origins of the excellent performances.